Sustainability Goals in Economic Policy — Legal Considerations - Stefan Bechtold (Wirtschaftsdienst, 2022)
Abstract In Europe, legislators are increasingly introducing sustainability goals into the system of private law. By prohibiting certain conduct, increasing transparency, nudging companies, as well as changing institutions, procedures and liability regimes, legislators complement private law with tools and goals traditionally attributed to public law. This article provides an overview and points to critical aspects, including the limited empirical evidence on how effective such measures are, whether such measures invite strategic maneuvers by companies, and how this affects the general relationship between private and public law.